Dampak Hukum Penyidikan Polri terhadap Tindak Pidana Di Sektor Jasa Keuangan - Andriyani, Fingky Ayu; Wanodyo Sulistyani; Atmaja, Budi Arta (JURNAL USM LAW REVIEW, 2025)
This study aims to examine the validity of evidence obtained by the Indonesian National Police in investigating criminal offenses in the financial services sector during the transitional period between the enactment of the PPSK Law and the Constitutional Court Decision No. 59/PUU-XXI/2023. The urgency of the study lies in the absence of transitional legal norms, which have created legal uncertainty and a potential formal defect in the admissibility of evidence within the criminal justice process. This research adopts a normative juridical method by combining statutory, case-based, and conceptual approaches. The findings reveal that police investigations during this period conflicted with the principles of legality and due process of law, rendering the resulting evidence formally invalid. The novelty of this research lies in its focus on the legal consequences of transitional normative gaps and the need for active judicial oversight in assessing the legality of investigative authority. Therefore, this study recommends the establishment of explicit transitional provisions for any shift in investigative authority and the issuance of judicial guidelines by the Supreme Court to ensure the integrity of evidentiary processes in the criminal justice system.   Penelitian ini bertujuan untuk mengkaji keabsahan alat bukti hasil penyidikan Polri terhadap tindak pidana di sektor jasa keuangan selama masa transisi antara berlakunya UU PPSK hingga Putusan MK Nomor 59/PUU-XXI/2023. Urgensi penelitian ini terletak pada kekosongan norma transisional yang menyebabkan ketidakpastian hukum dan potensi cacat formil pada alat bukti dalam proses peradilan pidana. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan undang-undang, kasus konkret, dan konsep hukum. Hasil analisis menunjukkan bahwa penyidikan oleh Polri dalam periode tersebut bertentangan dengan asas legalitas dan due process of law, sehingga alat bukti yang diperoleh seharusnya dinyatakan tidak sah secara formil. Kebaruan dari penelitian ini terletak pada sorotan terhadap implikasi yuridis dari kekosongan norma transisional dan perlunya kontrol yudisial yang aktif dari hakim dalam memverifikasi kewenangan penyidik. Oleh karena itu, penelitian ini merekomendasikan pembentukan norma transisi eksplisit dalam setiap perubahan kewenangan penyidikan dan penyusunan pedoman yudisial oleh Mahkamah Agung guna menjamin integritas proses pembuktian dalam sistem peradilan pidana.